Anal Cytological Lesions and HPV Infection in Individuals at Increased Risk for Anal Cancer. Issue 7 (25th April 2018) - Donà, Maria Gabriella; Benevolo, Maria; Latini, Alessandra; Rollo, Francesca; Colafigli, Manuela; Frasca, Mirko; Zaccarelli, Mauro; Giglio, Amalia; Moretto, Domenico; Pescarmona, Edoardo; Cristaudo, Antonio; Giuliani, Massimo
Abstract : BACKGROUND: Anal cytology may be useful for evaluating lesions associated with human papillomavirus (HPV) in individuals at increased risk for anal cancer. METHODS: Liquid‐based cytology was used to assess anal cytological lesions among human immunodeficiency virus (HIV)–infected and HIV‐uninfected men who have sex with men (MSM). The Linear Array HPV genotyping test was used for HPV detection. RESULTS: This cross‐sectional study included 1021 MSM, of whom 388 were HIV‐infected (38.0%). Anal cytological lesions (atypical squamous cells of undetermined significance or more severe [ASCUS+]) were observed in 32.5% and 53.2% of the HIV‐uninfected and HIV‐infected individuals, respectively ( P  < .0001). The highest ASCUS + prevalence was observed among ≥45‐year‐old HIV‐uninfected MSM (37.3%) and 25‐to 29‐year‐old HIV‐infected MSM (66.7%). High‐grade squamous intraepithelial lesions (HSILs) peaked in ≥ 45‐year‐old HIV‐uninfected subjects and 35‐ to 39‐year‐old HIV‐infected subjects. Individuals with anal infections with high‐risk (HR) HPV types were 3 to 4 times more likely to have an ASCUS + report. An HPV‐16 and/or HPV‐18 infection increased the odds of HSIL or more severe cytology (HSIL+) for HIV‐infected MSM almost 4 times. MSM concurrently infected with HR and low‐risk HPVs were significantly more likely to have low‐grade squamous intraepithelial lesions or more severe cytology (LSIL+) than those infected with only HR types. No significant associations were found between cytological abnormalities and the HIV load and nadir and current CD4 + counts. CONCLUSIONS: The prevalence of anal cytological lesions is high in MSM, even in HIV‐infected individuals treated with combined antiretroviral therapy. In these subjects, HSILs occur more frequently and at a younger age in comparison with HIV‐uninfected counterparts. Specific diagnostic procedures should be implemented to manage individuals at increased risk for anal cancer with an abnormal anal Papanicolaou test. Cancer Cytopathol 2018;126:461‐70. © 2018 American Cancer Society. Abstract : Anal cytological lesions are very common in men who have sex with men, even in young human immunodeficiency virus–infected individuals treated with combined antiretroviral therapy. There is an urgent need for diagnostic procedures to evaluate these lesions in groups at increased risk for anal cancer.